Estudo de pontes com vigas I segmentadas pré-fabricadas de concreto protendido, utilizando o sistema de pré-tração e pós-tração - Basso, Fabiano (2018)
Nowadays the manufacture of I beams of bridges with section of multiple beams is made in the place using the preforming. However if these beams were prefabricated they could have more quality in executive aspects, in addition to all the advantages that the prefabrication provides. It is understood, however, that the use of the preform in the place of the assembly, provides economy in the transport and the logistics of the same. These two factors become decisive factors in choosing the precast system most of the time, rather than the prefabricated one. The great problem in using prefabrication for the execution of I-beams of bridges, is the usually expensive transportation and transportation logistics, in addition to the assembly that are often complex, making it impractical to pre-fabricate these elements. In this way, the present work has as an alternative to reduce the costs of manufacturing and especially the transport of the beams. The proposed solution is to perform these long beams in a segmented way, thus, the transport becomes simple, and may no longer be a decisive factor in the choice between systems. To verify this proposed solution, we studied a bridge model, obtained through a calculation memory of a real viaduct. After the adoption of the proposed model, a cross-section beam was calculated for three different execution situations: prefabricated with pre-tension; pre-cast in place with post-traction and prefabricated segmented with on-site assembly and post-traction use. The study of the sizing of the segmented beam indicated that only minimal passive reinforcement was required in the first stage of fabrication. When these beams arrive in the work, the segments are connected, using post-traction to obtain the beam with the final span. From the obtained geometries a technical study of the transport of the prefabricated and segmented beams was carried out. The simulation of the real cost of transport, involving the prefabricated beams, being transported in full, comparing with them being transported in a segmented way, showed great savings for the second case.